PHYTOCHEMICAL SCREENING AND IN VITRO EFFECTS OF Azadirachta indicaMETHANOL EXTRACTS ON CERCARIA OF Biomphalaria glabrata (FULafia Journal of Science and Technology, 2026)
Biomphalaria glabrata are freshwater snail vectors that harbor S. mansoni parasites, a major Neglected Tropical Disease in Nigeria and sub-Saharan Africa; responsible for schistosomiasis. This research investigated the cercaricidal effects of Azadirachta indica (A. indica) methanolic extracts on S. mansoni cercaria. Fresh A. indica leaves and stem-bark were removed, shade-dried and pound. Phytochemical screening and Soxhlet extraction were carried out. Concentrations at 0.5-5.0 μg/ml were prepared. Cercariae from B. glabrata snails were shed under 100W light bulb for 2 h. These were challenged with the leaf and stem bark extracts. Mortality of each concentration was observed under a stereo microscope at 10-60 min of post exposure (PE). Results revealed that the presence of bioactive compounds include alkaloids, flavonoids, tannins, saponins, cardiac glycosides and carbohydrate. Cardiac glycosides and carbohydrates were the most abundance in the leaf, while flavonoids and tannins were the most abundant in stem bark. A. indica extracts demonstrated cercaricidal effect in a dose and time-dependent pattern. Mortality was recorded at 1.0 μg/ml in 30 minutes, PE. At 5.0μg/ml, there was 100% mortality in 10-20 min of PE (19.00+0.58a and 20.00+0.00a). The LC50, for stem bark and leaves were valued at 2.72 and 2.79μg/l respectively. There was no significant difference in mean mortality (p > 0.05) of both leave and stem bark extract (LSD = 0.82 and 2.30), respectively. Control showed motility all through the 60 min of PE. Both stem bark and leaf extracts of A. indica, upon further investigation, could be developed into juvenile schistosomicidal agent
Keywords: Azadirachta indica; cercaricidal; in vitro; phytochemical; schistosomiasis